Infection With Clostridioides difficile Attenuated Collagen-Induced Arthritis in Mice and Involved Mesenteric Treg and Th2 Polarization - Schmidt, Christian Johann; Wenndorf, Katharina; Ebbers, Meinolf; Volzke, Johann; Müller, Michael; Strübing, Julia; Kriebel, Katja; Kneitz, Susanne; Kreikemeyer, Bernd; Müller-Hilke, Brigitte (Frontiers in Immunology, 2020)
Objectives: Rheumatoid arthritis is an autoimmune disease with multifactorial etiopathogenesis. Among the environmental factors, mucosal infections and the inducing pathobionts are gaining increasing attention. We here set out to explore the gut-joint-axis and the impact of Clostridioides difficile infection on subsequent arthritis. Methods: We combined C. difficile infection in DBA/1J × B10.Q F1 mice with collagen induced arthritis (CIA). Mice were infected via oral gavage and infection was monitored by weight loss, colonic histology and antibodies against bacteria. Scoring of arthritis was performed macroscopically. Intestinal microbiomes were analyzed and immune responses were monitored via quantification of transcription factor-specific mRNA isolated from the inguinal and mesenteric lymphnodes. Results: Infection with C. difficile VPI 10463 resulted in significant weight loss and severe colitis yet accelerated the reversal towards the original microbiome after antibiotic treatment. Spontaneous clearance of VPI 10463 infection reduced the incidence of subsequent CIA and led to mesenteric Treg plasticity that involved Th2 polarization. However, this attenuating effect was abrogated if VPI 10463 was eradicated via vancomycin followed by fecal microbiota transplantation. Moreover, VPI 10463 infection following the onset of CIA lacked therapeutic potential. Conclusion: Our results demonstrate that infection with C. difficile VPI10463 induced an inflammation of the gut that protected from subsequent arthritis development in mice. Both, microbial changes to the gut and immune cell mobilization and/or polarization may have contributed to arthritis protection. The prospect of potential therapeutic benefits resulting from C. difficile infections or some byproduct thereof call for further experiments that help elucidate exact mechanisms.